1997
DOI: 10.1207/s15327752jpa6903_7
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-A and Rorschach Indices Related to Depression and Conduct Disorder: An Evaluation of the Incremental Validity Hypothesis

Abstract: This investigation extends the earlier research by Archer and Gordon (1988) by examining the extent to which combining indices from the newly released MMPI-A and the revised Rorschach Comprehensive System furnishes incremental validity in terms of improved diagnostic prediction. The predictive accuracy of selected MMPI-A and Rorschach variables conceptually related to diagnoses of depression and conduct disorder were compared in a clinical sample of 152 adolescents. Results of multivariate analyses of variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…Archer and Krishnamurthy (1997) compared the utility of the MMPI-A and Rorschach (Exner's Comprehensive System) for distinguishing between Conduct Disorder and depression. In short, the MMPI-A did a better job of predicting diagnostic status with the Rorschach contributing only two variables that accounted for a small proportion of variance in a depression diagnosis, and none to a Conduct Disorder diagnosis.…”
Section: Other Validity Studiesmentioning
confidence: 99%
“…Archer and Krishnamurthy (1997) compared the utility of the MMPI-A and Rorschach (Exner's Comprehensive System) for distinguishing between Conduct Disorder and depression. In short, the MMPI-A did a better job of predicting diagnostic status with the Rorschach contributing only two variables that accounted for a small proportion of variance in a depression diagnosis, and none to a Conduct Disorder diagnosis.…”
Section: Other Validity Studiesmentioning
confidence: 99%
“…In a study of personality disorders, Blais, Hilsenroth, Castlebury, Fowler, and Baity (2001) found that each test was associated with unique variance in symptom scores but that this incremental validity varied across disorders. Similarly, a study using the adolescent version of the MMPI (Archer & Krishnamurthy, 1997) found evidence supporting the incremental validity of the some Rorschach variables (Vista and Affective Ratio for predicting depression) but not others (the Depression Index for predicting depression or various variables for predicting conduct disorder). In his critique of Wood et al (1999), Meyer (2000) reported new analyses of data he had presented earlier (Meyer, 1993) regarding the incremental validity of the SCZI above and beyond the information provided by the MMPI-2 Scale 8 and BIZ.…”
mentioning
confidence: 98%
“…This is true for both adults and adolescents. For example, six of eight studies conducted independently of the Rorschach Workshops found no significant relation between the revised DEPI and psychiatric diagnoses (Archer & Krishnamurthy, 1997;Ball, Archer, Gordon, & French, 1991;Caine, Frueh, & Kinder, 1995;Meyer, 1993;Ritsher, Slivko-Kolchik, & Oleichik, 2001;Sells, 1990Sells, / 1991; see also Meyer, 2001a), one study yielded mixed results (Ilonen et al, 1999), and only one study yielded unmixed positive results (Jansak, 1996(Jansak, /1997.…”
Section: Research On the Assessment Of Psychopathologymentioning
confidence: 99%